Intrastriatal injection of α-synuclein can lead to widespread synucleinopathy independent of neuroanatomic connectivity - Sorrentino, Zachary A. (Mol Neurodegener, 2017)
BACKGROUND: Prionoid transmission of α-synuclein (αSyn) aggregates along neuroanatomically connected projections is posited to underlie disease progression in α-synucleinopathies. Here, we specifically wanted to study whether this prionoid progression occurs via direct inter-neuronal transfer and, if so, would intrastriatal injection of αSyn aggregates lead to nigral degeneration. METHODS: To test prionoid transmission of αSyn aggregates along the nigro-striatal pathway, we injected amyloidogenic αSyn aggregates into two different regions of the striatum of adult human wild type αSyn transgenic mice (Line M20) or non-transgenic (NTG) mice and aged for 4 months. RESULTS: M20 mice injected in internal capsule (IC) or caudate putamen (CPu) regions of the striatum showed florid αSyn inclusion pathology distributed throughout the neuraxis, irrespective of anatomic connectivity. These αSyn inclusions were found in different cell types including neurons, astrocytes and even ependymal cells. On the other hand, intra-striatal injection of αSyn fibrils into NTG mice resulted in sparse αSyn pathology, mostly localized in the striatum and entorhinal cortex. Interestingly, NTG mice injected with preformed human αSyn fibrils showed no induction of αSyn inclusion pathology, suggesting the presence of a species barrier for αSyn fibrillar seeds. Modest levels of nigral dopaminergic (DA) neuronal loss was observed exclusively in substantia nigra (SN) of M20 cohorts injected in the IC, even in the absence of frank αSyn inclusions in DA neurons. None of the NTG mice or CPu-injected M20 mice showed DA neurodegeneration. Interestingly, the pattern and distribution of induced αSyn pathology corresponded with neuroinflammation especially in the SN of M20 cohorts. Hypermorphic reactive astrocytes laden with αSyn inclusions were abundantly present in the brains of M20 mice. CONCLUSIONS: Overall, our findings show that the pattern and extent of dissemination of αSyn pathology does not necessarily follow expected neuroanatomic connectivity. Further, the presence of intra-astrocytic αSyn pathology implies that glial cells participate in αSyn transmission and possibly have a role in non-cell autonomous disease modification. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13024-017-0182-z) contains supplementary material, which is available to authorized users.